Funding the Housing for the Low-Income People through Waqf based Cooperatives - Rohollah Shahnazi; Parviz Rostamzadeh; Seyed Mohammad Hashem Pourmola; Maryam Balaie (جستارهای اقتصادی, 2019)
Low-income people are struggling to find housing. The purpose of this article is to present a housing financing solution for low-income people in the framework of Waqf-bonds through cooperatives. Then, the field survey method was used to measure the acceptance of the Waqf funds in the form of a willingness to pay questionnaire. The results show that the Waqf fund can be theoretically designed in three modes: In the first case, the assets of the Waqf funds are used directly to finance housing; in the second case the profits of this fund are used to finance housing; in the last case, the profits of assets in Waqf funds and the interests of the cooperative based Waqf funds are allocated to the construction of housing and finally the mail sources are invested. Also, the results of the questionnaire show that most people tend to pay more than their taxes for low-income housing. And variables such as tax rates, trust in the Waqf organization, and increased efficiency of housing by benevolent and charitable acts has a positive effect on the willingness of benevolent persons to finance the housing for the low-income people.